2009
DOI: 10.1002/jbio.200910013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical optical coherence tomography combined with multiphoton tomography of patients with skin diseases

Abstract: We report on the first clinical study based on optical coherence tomography (OCT) in combination with multiphoton tomography (MPT) and dermoscopy. 47 patients with a variety of skin diseases and disorders such as skin cancer, psoriasis, hemangioma, connective tissue diseases, pigmented lesions, and autoimmune bullous skin diseases have been investigated with (i) state-of-the-art OCT systems for dermatology including multibeam swept source OCT, (ii) the femtosecond laser multiphoton tomograph, and (iii) dermosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 27 publications
(19 reference statements)
0
57
0
5
Order By: Relevance
“…OCT was performed with a swept source centered at 1300 nm and provided simultaneous largearea screening of simple microsphere specimens to demonstrate the spatial coregistration in the small intestine and ear tissues of mouse models ex vivo. König et al 200 reported the first clinical study with a variety of skin diseases and disorders, such as skin cancer, psoriasis, hemangioma, connective tissue diseases, pigmented lesions, and autoimmune bullous skin diseases. Two different OCT systems were combined with MPT and dermoscopy to provide 2-D color images of the skin surface.…”
Section: Multimodal Oct and Mpmmentioning
confidence: 99%
“…OCT was performed with a swept source centered at 1300 nm and provided simultaneous largearea screening of simple microsphere specimens to demonstrate the spatial coregistration in the small intestine and ear tissues of mouse models ex vivo. König et al 200 reported the first clinical study with a variety of skin diseases and disorders, such as skin cancer, psoriasis, hemangioma, connective tissue diseases, pigmented lesions, and autoimmune bullous skin diseases. Two different OCT systems were combined with MPT and dermoscopy to provide 2-D color images of the skin surface.…”
Section: Multimodal Oct and Mpmmentioning
confidence: 99%
“…This system was capable of acquiring wide area mosaics ($1 Â 1 mm 2 ) of in vivo human skin. A clinical study investigating a variety of skin diseases such as psoriasis, pemphigus vulgaris and melanocytic lesions in vivo using the clinical MPT system, DermaInspect (JenLab GmbH, Jena, Germany) and two OCT systems (EX1301, Michelson diagnostics, UK; Callisto, Thorlabs GmbH, Germany) operated in two-dimensional (2D) mode, demonstrated the potential of MPT/OCT multimodal imaging technology for dermatological diagnostic applications [30]. However, more systematic studies using 3D multimodal MPT/OCT systems are required to identify and characterize dermatological disorders with high sensitivity and specificity.…”
Section: Biophotonicsmentioning
confidence: 99%
“…A combined system could perform a fast OCT scan to find a region of interest, which would subsequently be examined in detail with MPT. In a recent study, König et al demonstrated with correlated OCT and MPT images of skin cancer lesions diagnostic potential of combining these modalities [252]. Already in 2006, Vinegoni et al presented a combined MPT/OCM system that provides overlaid morphologic and spectroscopic images of different samples [253].…”
Section: Combination Of Modalitiesmentioning
confidence: 99%